(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Physical and mechanical properties of Bambusa vulgaris and Schizostachyum brachycladum were investigated. The sample were classified into two different ages which are young and mature for each culm of bamboo. The aim of this study to investigate the physical properties such as density, basic density, moisture content, water absorption and thickness swelling. Other than that, the mechanical properties also help to determine their flexural test for modulus of rupture (MOR) and modulus of elasticity (MOE). The method used to analyse physical and mechanical properties were following the ISO standard. From this study, young Bambusa vulgaris has indicated the higher content of moisture content, water absorption and thickness swelling with 67.66%, 2.69% and 34.03%, respectively while mature Schizostachyum brachycladum has shown the higher value in basic density, density, and flexural test for MOR and MOE with 876.33 kg/m3, 1084.49 kg/m3, 317.01 N/mm2 and 122986.18 N/mm2, respectively.